Acute inflammatory response in Nile tilapia fed probiotic Lactobacillus plantarum in the diet - doi: 10.4025/actascibiolsci.v33i3.8011 - Dotta, Geovana (2011)
The present study evaluated the acute inflammatory response induced by carrageenin (500 µg) injected in the swim bladder of Nile tilapia, after fed or not probiotic supplemented diet. Fifty four fish were distributed in six treatments and three replicates: Group A: Fish fed unsupplemented diet: 0.5 mL saline-injected fish; fish injected with 500 µg carrageenin diluted in 0.5 mL saline; Non-injected. Group B: Fish fed probiotic supplemented diet: saline-injected fish; carrageenin-injected fish; Non-injected. Fifteen days after feeding the fish were injected with carrageenin or saline. After six hours, inflammatory exudate was collected, as well as the blood for hematocrit, red blood cell (RBC) and white blood cell (WBC) counts, differential count of leucocytes and phagocytic activity in the blood. Supplementation with probiotic did not influence the RBC, hematocrit and the numbers of lymphocytes and basophils in the blood. The number of neutrophils was significantly higher in supplemented fish injected with carrageenin. Glucose concentration in supplemented and non-injected fish was higher than that observed in the saline injected ones. Probiotic potentialized the migration of cells to the inflammatory focus in the animals injected with the carrageenin irritant. In fish injected with saline and carrageenin occurred the greatest phagocytic activity in the blood in relation to those treatments.